Pengembangan Aplikasi E-Form Daftar Seleksi Bahan Perpustakaan di Perpustakaan Nasional RI - Yulianah Yulianah (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2022)
Library material selection is one of the main tasks performed by librarians at National Library of Indonesia in the implementation of library collection development. Compilation of library material selection list, especially foreign monographs, performed by librarians often results in diverse format, incomplete fill in bibliography description, inaccurate pricing, less effective and efficient in the process. It is caused by no standard format in compiling of foreign monographs library material selection list assigned as reference for librarians. This research uses software engineering approach to produce e-form application prototype of library material selection list. Data is collected by interview with stakeholders. Development of e-form application of library materials selection list was designed according topredefined standard format. This research has succeeded in developing application that can improve effectiveness and efficiency in compiling library material selection list, therefore the next workflow, acquisiton of library collection in National Library of Indonesia, can be achieved quickly, precisely, and accurately.